Teaching English Speaking in Myanmar: A Phenomenological Exploration of Teachers’ Experiences - Hpawdaw, Htu Pan; Katenga, Josephine; Kachchhap, Sandeep Lloyd (International Journal of Language and Literary Studies, 2025)
This study investigates the lived experiences of five non-native English teachers responsible for teaching speaking skills at a high school in Myanmar. Using a descriptive phenomenological approach, it examines how these teachers perceive and navigate the complexities of speaking instruction within a multilingual, resource-limited, and politically unstable environment. Data were collected through semi-structured interviews and a focus group, providing rich insights into their instructional practices and coping strategies. Teachers reported challenges such as low confidence in oral English, limited training in communicative methodologies, inadequate resources, and systemic pressures that prioritize exam-oriented learning over spoken proficiency. These constraints often lead to reliance on translation, rote memorization, and traditional drills, with only sporadic attempts at interactive or student-centered approaches. Despite these limitations, teachers actively negotiate their roles and adapt strategies to foster speaking skills where possible. The findings highlight the urgent need for targeted professional development and institutional support that enable teachers to implement communicative, context-sensitive approaches to speaking instruction in Myanmar’s high schools.